HUBUNGAN PENGETAHUAN TENTANG COVID-19 DENGAN PENERAPAN PROTOKOL KESEHATAN MASYARAKAT DI RSUD DR. R.SOEDJATI SOEMADIARJO PURWODADI KABUPATEN GROBOGAN: Array - Suryani Suryani; Mun Aminah (Yayasan Citra Dharma Cindekia, 2022)
Covid-19 is an unprecedented infectious disease. The Covid-19 virus is a virus that is transmitted to humans and attacks the respiratory system. This is a serious world problem with the number of cases always increasing. On March 11, 2020, the World Health Organization declared it a pandemic. One of the cities that is unavoidable from Covid-19, namely Grobogan Regency, it was found that the data update on the Grobogan Regency Kominfo situation on October 23, 2020 reported that 22 people were being treated in health facilities, 20 people were self-isolating and 78 people died. The act of implementing the health protocol is the key in preventing the spread of Covid-19, but many people do not implement it. This happens because of ignorance or unwillingness of the community to implement health protocols. Therefore, it is necessary to know about public knowledge with the application of health protocols during a pandemic. The purpose of this study was to determine the relationship between knowledge about Covid- 19 and the application of public health protocols at RSUD Dr. R. Soedjati Soemodiarjo Purwodadi, Grobogan Regency. The research method is a quantitative study using a cross sectional approach, the population of this study is the inpatient caretaker, the sampling technique used is non-probability sampling with accidental sampling technique and obtained a sample of 77 respondents. The results of the bivariate analysis obtained a p value (0.0000) < (0.05) and an R value of 1, which means that there is a relationship between knowledge about Covid-19 and the application of community protocols at Dr. R. Soedjati Soemodiarjo Hospital, Purwodadi, Grobogan Regency and has a strong correlation